Hazardous and Toxic Waste Management with Health-Friendly Solidification Technology: An Overview - Ramlia Wati; Zuriat Hidayani; Aulia Maghfirah Alifia; Dilla Dilla (Journal of Health Science and Pharmacy, 2026)
Background: B3 waste (Toxic and Hazardous Materials) is the residue of business activities that contain hazardous and toxic substances (B3) that have a high risk of causing environmental contamination and threatening the safety of living beings. Handling this waste, especially from the health service sector, is very important because of the potential for the spread of infections and pollution of soil, water, and air. Therefore, B3 Waste management is required to follow strict technical standards, as stipulated in regulations, such as Government Regulation No. 101 of 2014. Objective: This literature review aims to identify the main challenges in B3 Waste management, evaluate regulatory frameworks, and analyze efficient strategies, emphasizing the role of Solidification/Stabilization (S/S) technology to achieve a sustainable waste management system. Methods: This research uses a literature review methodology, in which data is collected from various scientific journals accessed through Google Scholar and general search engines. Strict criteria are applied in the selection, including topic suitability, most recent publication date, and availability of articles in full-text format Results: Key findings indicate that B3 Waste management is constrained by low regulatory compliance and lack of treatment infrastructure. The proposed solutions include tightening law enforcement (the principle of absolute responsibility), the development of technological innovations (such as S/S to reduce hazards and recycle waste into construction materials), as well as increased socialization and technical competence. Conclusion: An integrated and comprehensive approach is needed to manage B3 Waste. Success depends on the synergy between strong regulations, the application of advanced processing technologies (such as S/S), and the strengthening of the capacity of technical personnel to reduce the adverse effects of waste and achieve environmental sustainability. Keywords: B3 Waste, Solidification/Stabilization (S/S), Absolute Responsibility, Treatment Technology, Environmental Health.